2012
DOI: 10.1037/a0030306
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive mechanisms for transitive inference performance in rhesus monkeys: Measuring the influence of associative strength and inferred order.

Abstract: If Ben is taller than Emily and Emily is taller than Dina, one can accurately infer that Ben is taller than Dina. This process of inferring relations between stimuli based on shared relations with other stimuli is called transitive inference (TI). Many species solve TI tasks in which they learn pairs of overlapping stimulus discriminations (A+B−, B+C−, etc.) and are tested with non-adjacent novel test pairings (e.g. BD). When relations between stimuli are determined by reinforcement (i.e., A is reinforced when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
67
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 76 publications
12
67
1
Order By: Relevance
“…3, the birds showed no preference for either stimulus during Block 1 of probe testing but then rapidly developed a clear preference for C during the later blocks (Figure 2f). In their list-linking study of rhesus macaques, Gazes et al (2012) also found above-chance performance on far-between pairs. Because they used longer lists, there were more far-between exemplars to analyze.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3, the birds showed no preference for either stimulus during Block 1 of probe testing but then rapidly developed a clear preference for C during the later blocks (Figure 2f). In their list-linking study of rhesus macaques, Gazes et al (2012) also found above-chance performance on far-between pairs. Because they used longer lists, there were more far-between exemplars to analyze.…”
Section: Discussionmentioning
confidence: 99%
“…In Treichler's studies the error rates for pairs below the link were roughly double those of corresponding pairs above it (Table 2 in Treichler & Van Tilburg, 1996;Figure 12.3 in Treichler, 2007). In Gazes et al (2012), multiple comparisons were analogous to B ? D versus 2 ?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations